From euclid to corner sums - a trail of telescoping tricks - Patrício, Pedro (2021)
Euclid's algorithm is extended to binomials, geometric sums and corner sums. Two-sided non-commuting, non-constant linear difference equations will be solved, and the solution is applied to corner sums, thereby presenting an explicit formula for the generator of the bi-module spanned by the two starting corner sums.